2021
DOI: 10.3389/fpubh.2021.712584
|View full text |Cite
|
Sign up to set email alerts
|

A Multiethnic Asian Perspective of Presumed Consent for Organ Donation: A Population-Based Perception Study

Abstract: Background: Organ shortage is still a world-wide problem, resulting in long waiting lists for kidney, liver, and heart transplant candidates across many transplant centers globally. This has resulted in the move toward presumed consent to increase deceased organ donation rates. However, there remains a paucity of literature on public attitude and barriers regarding the opt-out system, with existing studies limited to Western nations. Therefore, this study aimed to understand public sentiment and different barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…27 While presumed consent is thought to increase transplant rates, its true impact on increasing organ donation rates is questionable. 28 In contrast, a study from an Asian country like Singapore which is a diverse and multi-ethnic society reported that the organ donation rates remain low, albeit presumed consent legislation, due to patient-level barriers, including but not limited to knowledge gaps, cultural values, religious backgrounds, and emotional impact at relatives' death. 28 This finding is consistent with the present study findings.…”
Section: Discussionmentioning
confidence: 99%
“…27 While presumed consent is thought to increase transplant rates, its true impact on increasing organ donation rates is questionable. 28 In contrast, a study from an Asian country like Singapore which is a diverse and multi-ethnic society reported that the organ donation rates remain low, albeit presumed consent legislation, due to patient-level barriers, including but not limited to knowledge gaps, cultural values, religious backgrounds, and emotional impact at relatives' death. 28 This finding is consistent with the present study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some European countries have "opt-out," i.e., presumed consent systems, in which no explicit consent is required for a person to become a potential donor [197]. However, most Asia-Pacific countries except Singapore have an "opt-in" policy that requires explicit consent from first-degree relatives of the potential donor [348].…”
Section: Deceased Donormentioning
confidence: 99%